(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Several studies have identified young people's food habits and preferences in Nigeria and found a strong preference for fast foods, snacks, and fizzy drinks. Indeed, there is a growing concern about the dietary quality of ultra-processed foods. However, little is known about the role of adequate food skills in an individual's choice of a quality meal. This study examined food skills as a predictor of diet quality among pregnant. The participants comprised two hundred eleven (n-211) pregnant women attending ante-natal care in the River State Teaching Hospital. The respondents completed a self-report measure of food skills and healthy food choices. The result revealed a statistically significant interaction between food skills and food choice F (1,209), 38.17, P<.000. Thus, it was recommended that food skills are an essential determinant of healthy food choices. The result has implications for healthy child development.